2015
DOI: 10.3168/jds.2015-9971
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Changes in fluorescence intensity induced by soybean soluble polysaccharide–milk protein interactions during acidification

Abstract: Interactions between stabilizer and milk protein are believed to influence the stabilizing behavior of the milk system. We investigated changes in fluorescence intensity induced by interactions of soybean soluble polysaccharide (SSPS) and milk protein (Mp) during acidification. The fluorescence intensity (If) of Mp increased as pH decreased from 6.8 to 5.2. Compared with Mp alone, If of SSPS-Mp mixtures increased as the pH decreased from 6.8 to 5.2. We found that the If of the SSPS-Mp mixture decreased in a pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This indicates that the tryptophan residues of α-amylase are moving to a less polar environment after binding with λ-carrageenan. The degree of quenching of the α-amylase/λ-carrageenan 10:1 mixture was the largest, suggesting they had a strong binding interaction [ 31 ]. After the second PEF cycle, the fluorescence intensity of α-amylase alone decreased dramatically, and the quenching rate reached more than 60%.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that the tryptophan residues of α-amylase are moving to a less polar environment after binding with λ-carrageenan. The degree of quenching of the α-amylase/λ-carrageenan 10:1 mixture was the largest, suggesting they had a strong binding interaction [ 31 ]. After the second PEF cycle, the fluorescence intensity of α-amylase alone decreased dramatically, and the quenching rate reached more than 60%.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to HMP, it is suggested that SSPS prevents aggregation of casein mainly by the steric repulsion, and the electrostatic repulsion is auxiliary [3,28]. The electrostatic interaction between SSPS and casein plays a major role in the formation of complexes [30].…”
Section: Introductionmentioning
confidence: 98%